Perceived barriers to and facilitators of being physically active during adjuvant cancer treatment. Issue 7 (July 2016) - Henriksson, Anna; Arving, Cecilia; Johansson, Birgitta; Igelström, Helena; Nordin, Karin
Highlights: Several barriers addressed by participants can be alleviated by physical activity. Participants expressed a wish to receive professional help to be physically active. Early intervention and information from health care professionals might be beneficial. Abstract: Objective: The aim was to describe cancer patients' perceived barriers and facilitators of physical activity during adjuvant cancer treatment. Methods: Semi-structured focus group interviews were conducted with patients with breast cancer ( n = 9) and colorectal cancer ( n = 1) and prostate cancer ( n = 8) undergoing adjuvant cancer treatment. To capture perceived barriers and facilitators before starting treatment, individual interviews with women with breast cancer ( n = 5) were also conducted. 23 patients in total, were interviewed, and the transcribed interviews were analysed with qualitative content analysis. Results: Three categories emerged: "Physical and emotional barriers"—addresses experiences of side-effects, co-morbid conditions and emotional barriers, preventing physical activity (PA). "Perspective and attitudes"—how self-efficacy, self-image, preference, concerns, expectations, experience and new perspective regarding one's health influencing PA. "Support and practicalities"—addresses needs of support and information and how practicalities could be a barrier to PA. Conclusions: Several barriers were side effects of oncological treatment, which can be alleviated by PA. Another barrier was concerns regarding safety of PA during treatment. Communicating benefits and safety of PA to cancer patients early as possible after diagnosis might be beneficial. Practice implications: Information about PA from health care staff should be given early after diagnosis and as a part of standard care.